ANALISIS ISI KOMENTAR NETIZEN PADA IKLAN SHAMPOO REJOICE 3IN1 X KIKI SAPUTRI #RAMBUTNODRAMA (Universitas Negeri Surabaya, 2023)
This research discusses the response of netizens to the Rejoice3in1 version of Kiky Saputri in the YouTube ad RambutNoDrama